Poglavja iz zgodovine prekmurskega knjižnega jezika - Jesenšek, Marko (University of Maribor Press, 2013)
Chapters from the History of the Prekmurje Literary Language. The monograph covers the most important chapters in the development of the Prekmurje language from its inception (Temlin, 1715) to the translation of Scripture (Š. KüzMIč, 1771), the Catholic continuation (M. Küzćim), and development in the 19th century. An important realization is that in the mid-19th century Prekmurje literary language was unified with the Central Slovenian language; in Prekmurje, such natural development was embraced by Catholic writers, while Protestants persisted in provincialism until the end of World War I. Jesenšek thus raises a topical and important issue for science, as he recognizes the implications for unscientific vendor theory, which he refutes by analyzing the language situation in Prekmurje. For further linguistic research, it is important that Kardoš’s insistence on the Prekmurje language in the book, after unification of the Slovene literary norm, not explain the linguistic delusion and deviation from the positive developmental direction of the Slovene language, but analyze his posture sociolinguistically and show it in the light of the then hidden Hungarian pressures: not as a decision for Hungary and against Slovenia, but as a decision to survive Protestantism in Prekmurje.